Physical and Meiotic Mapping of the Region of Human Chromosome 4q11–q13 Encompassing the Vitamin D Binding Protein DBP/Gc-Globulin and Albumin Multigene Cluster - Song, Young-Han; Naumova, Anna K.; Liebhaber, Stephen A.; Cooke, Nancy E. (Genome Research, 1999)
The vitamin D binding protein/Gc-globulin (DBP) gene is a member of a multigene cluster that includes albumin (ALB), α-fetoprotein (AFP), and α-albumin/afamin (AFM). All four genes have structural and functional similarities and map to the same chromosomal regions in humans (4q11–q13), mice, and rats. An accurate physical map of the region encompassing these genes is a prerequisite for study of their respective transcriptional regulation and identification of potential shared regulatory elements. By refining the physical and meiotic maps of the 4q11–q13 region and creating a local PAC contig, the order and transcriptional orientations of these four genes were determined to be centromere–3′-DBP-5′–5′-ALB-3′–5′-AFP-3′–5′-AFM3′–telomere. The ancestral DBP gene was separated from the ALBgene by >1.5 Mb. This organization and spacing establishes a foundation for ongoing functional studies in this region.